2015
DOI: 10.18388/abp.2015_1081
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of polygalacturonase in solid-state fermentation: selection of the process conditions, isolation and partial characterization of the enzyme

Abstract: Polygalacturonase (PG) production by Penicillium chrysogenum during solid-state fermentation was accompanied by decomposition of orange peels. A leaching procedure was developed through the selection of solvent, time and intensity of stirring. A maximum PG activity was observed after 48 h peel inoculation. Further cultivation decreased the enzyme activity significantly, up to 60% of the maximum PG activity. During fermentation, a rapid acidification of the solid medium which inhibited the pectinolytic enzyme, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Natural pH and 6.0 were found to be suitable for enhancing polygalacturonase production (Figure 2a), which is supported by the finding of Patil et al [3] Zasłona and Trusekhołownia [7] have reported that the most promising production was obtained when the pH was 8.0. But Sethi et al [9] reported that pH 5.0 was optimum for the production of pectinase by Aspergillus terreus NCFT 4269.10.…”
Section: Optimization Of Fermentation Conditions For Enhancing Polygasupporting
confidence: 73%
See 3 more Smart Citations
“…Natural pH and 6.0 were found to be suitable for enhancing polygalacturonase production (Figure 2a), which is supported by the finding of Patil et al [3] Zasłona and Trusekhołownia [7] have reported that the most promising production was obtained when the pH was 8.0. But Sethi et al [9] reported that pH 5.0 was optimum for the production of pectinase by Aspergillus terreus NCFT 4269.10.…”
Section: Optimization Of Fermentation Conditions For Enhancing Polygasupporting
confidence: 73%
“…Sethi et al [9] and Maller et al [23] have also reported that A. terreus and A. niveus produced pectinase optimally at 4 d of incubation, which is in agreement with current finding in this research. But the maximum polygalacturonase activity was observed after 3 d by using Penicillium variotii [3] and Penicillium chrysogenum [7] , and at 5 d by using Penicillium atrovenetum [24] , respectively. The reason might be that the natural substrate induced the enzyme production at various phase for different strains.…”
Section: Effects Of Fermentation Timementioning
confidence: 99%
See 2 more Smart Citations
“…The pH optima of purified PGs determines its possible application like fruit juice clarification, retting of natural fibers etc. It has been observed that most of the fungal PGs have pH optima 3–6 (Patil et al 2012 ; Yadav et al 2012 ; Kant et al 2013 ; Martins et al 2013 ; Castruita-Domínguez et al 2014 ; Ortega et al 2014 ; Chen et al 2014 ; Zhou et al 2015 ; Zaslona and Trusek-Holownia 2015 ; Pan et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%